Low-cost rapid detection of rifampicin resistant tuberculosis using bacteriophage in Kampala, Uganda - Smith Peter G; Jones-Lopez Edward C; Kayes Susan; Narayan Kalpana; Mumbowa Francis; Joloba Moses L; Mallard Kim; Ogwang Sam; Traore Hamidou; Ellner Jerrold J; Mugerwa Roy D; Eisenach Kathleen D; et al. (BMC, 2007)
Abstract Background Resistance to anti-tuberculosis drugs is a serious public health problem. Multi-drug resistant tuberculosis (MDR-TB), defined as resistance to at least rifampicin and isoniazid, has been reported in all regions of the world. Current phenotypic methods of assessing drug susceptibility of M. tuberculosis are slow. Rapid molecular methods to detect resistance to rifampicin have been developed but they are not affordable in some high prevalence countries such as those in sub Saharan Africa. A simple multi-well plate assay using mycobacteriophage D29 has been developed to test M. tuberculosis isolates for resistance to rifampicin. The purpose of this study was to investigate the performance of this technology in Kampala, Uganda. Methods In a blinded study 149 M. tuberculosis isolates were tested for resistance to rifampicin by the phage assay and results compared to those from routine phenotypic testing in BACTEC 460. Three concentrations of drug were used 2, 4 and 10 μg/ml. Isolates found resistant by either assay were subjected to sequence analysis of a 81 bp fragment of the rpoB gene to identify mutations predictive of resistance. Four isolates with discrepant phage and BACTEC results were tested in a second phenotypic assay to determine minimal inhibitory concentrations. Results Initial analysis suggested a sensitivity and specificity of 100% and 96.5% respectively for the phage assay used at 4 and 10 μg/ml when compared to the BACTEC 460. However, further analysis revealed 4 false negative results from the BACTEC 460 and the phage assay proved the more sensitive and specific of the two tests. Of the 39 isolates found resistant by the phage assay 38 (97.4%) were found to have mutations predictive of resistance in the 81 bp region of the rpoB gene. When used at 2 μg/ml false resistant results were observed from the phage assay. The cost of reagents for testing each isolate was estimated to be 1.3US$ when testing a batch of 20 isolates on a single 96 well plate. Results were obtained in 48 hours. Conclusion The phage assay can be used for screening of isolates for resistance to rifampicin, with high sensitivity and specificity in Uganda. The test may be useful in poorly resourced laboratories as a rapid screen to differentiate between rifampicin susceptible and potential MDR-TB cases.